ANALISIS PERBEDAAN RATIO DECIDENDI HAKIM DALAM PUTUSAN PERSETUBUHAN SUKA SAMA SUKA OLEH ANAK DI INDONESIA - Larasati Larasati; Eka Nanda Ravizki (Jurnal Ilmiah Advokasi, 2026)
Differences in the application of legal provisions to cases involving consensual sexual intercourse between minors continue to reveal disparities in judges' ratio decidendi, even where the cases share substantially similar factual characteristics. Such disparities may undermine legal certainty and affect the effectiveness of legal protection afforded to children, both as victims and as offenders, within Indonesia's juvenile criminal justice system. This study aims to analyze the differences in the ratio decidendi adopted by judges in Decision No. 27/Pid.Sus-Anak/2023/PN Smr and Decision No. 4/Pid.Sus-Anak/2024/PN Kdr and to examine their implications for child legal protection in Indonesia. This research employs a normative legal method using statutory, case, and conceptual approaches. The analysis is conducted qualitatively by examining legislation, legal doctrines, and the two court decisions through legal interpretation and comparative analysis of the judges' ratio decidendi. The findings demonstrate that the differences in judicial reasoning are primarily influenced by the legal construction of the facts and the judges' interpretation of the concept of a child's consent. In Decision No. 27/Pid.Sus-Anak/2023/PN Smr, the court applied Law No. 12 of 2022 on Sexual Violence Crimes because the victim was unconscious due to alcohol intoxication and was therefore considered incapable of providing valid consent. Conversely, in Decision No. 4/Pid.Sus-Anak/2024/PN Kdr, the court relied on the Child Protection Law, reasoning that the victim's status as a minor legally invalidated any purported consent, notwithstanding the consensual nature of the relationship. The novelty of this study lies in its comparative analysis of the ratio decidendi employed in two judicial decisions involving highly comparable factual circumstances but resulting in different legal frameworks and judicial reasoning. The study concludes that harmonized judicial interpretative guidelines are necessary to ensure greater consistency in court decisions, strengthen legal certainty, and enhance the effectiveness of child protection in accordance with the principle of the best interests of the child.Keywords: Ratio decidendi; Child Protection; Consensual Sexual Intercourse Involving Minors; Sexual Violence Crimes; Juvenile Criminal Justice System